Adalimumab in the management of Behçet’s disease - Ueda A; Takeno M; Ishigatsubo Y (Dove Medical Press, 2015)
Atsuhisa Ueda, Mitsuhiro Takeno, Yoshiaki Ishigatsubo Department of Internal Medicine and Clinical Immunology, Graduate School of Medicine, Yokohama City University, Yokohama, Japan Abstract: Behçet’s disease (BD) is a relapsing, systemic, inflammatory disorder that affects various organ systems. Most of the manifestations of BD are self-limiting, but ocular attacks are an exception. Gastrointestinal tract, central nervous system, and cardiovascular system manifestations are relatively infrequent but may be resistant to conventional immunosuppressive treatment and therefore life-threatening. Tumor necrosis factor alpha antagonists are increasingly being used in patients whose BD is inadequately controlled by standard immunosuppressive regimens. Most of the current experience regarding the treatment of refractory BD involves the use of infliximab; however, adalimumab has also been successfully used in cases of BD refractory to both conventional therapy and infliximab. Compared with infliximab, adalimumab offers several other advantages, such as the ability to self-administer at home, better patient compliance, and an improved side effect profile. Here, we review clinical experience of the use of adalimumab to treat the serious manifestations of BD. Adalimumab is a promising drug for the treatment of BD, and its randomized, prospective study in a large number of patients is warranted to fully determine its efficacy in the refractory BD setting. Keywords: adalimumab, Behçet’s disease, intestinal BD, infliximab, ocular lesion, central nervous system